PERAN IKLAN TIKTOK DALAM MEMBENTUK MINAT BELI MAHASISWA PADA BRAND BUSANA PERSPEKTIF ETIKA PEMASARAN SYARIAH - Zamzami, Muhammad; Sunarto, Andang; Harpepen, Andi; Ujang Sanusi (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to examine the role of TikTok advertisements in shaping students' buying interest in fashion brands and the perspective of Sharia marketing ethics on these TikTok advertisement practices. This study uses a qualitative approach with the type of field research. Informants were selected using purposive sampling technique, totaling 9 active students from the Faculty of Islamic Economics and Business at UINFAS Bengkulu who use TikTok and have been exposed to fashion brand advertisements. Data collection was conducted through interviews, observation, and documentation. The results indicate that TikTok advertisements for fashion brands play a real role in shaping students' buying interest through four functions: informing, by clearly conveying fashion product information to attract attention; influencing, by affecting through visual appeal and content creativity; reminding, by maintaining students' memory of the brand and product; and adding value, by encouraging concrete actions up to purchase. From the perspective of sharia marketing ethics, the justice of Al-'Adl has been well fulfilled; however, the honesty of Shiddiq and the responsibility of Amanah have not been optimally fulfilled, as indicated by the tendency of sellers to only convey product advantages, inconsistency between advertisement appearance and the product received, and untimely delivery. This study concludes that there is still a gap between TikTok advertising practices by fashion brands and Islamic ethical values that need to be improved.